Motivation to learn transforming classroom culture to support student achievement - Middleton, Michael; Perks, Kevin (Classroom insights from educational psychology, 2014)
Harness the power of motivation to transform the learning experience! When properly channeled, motivation propels learning forward. Yet teachers across all grade levels and disciplines struggle to recognize and cultivate this dynamic, social force in the classroom. This essential resource proves that all students are motivated to learn, and provides authentic tools to create and sustain a classroom community that is highly engaged. You'll discover: Reflection activities that promote student voice and self-efficacy as well as assess existing motivation levels, Case studies and best practices based on current motivation theory and research, Strategies to design meaningful learning tasks and build positive relationships with students and colleagues. ... Provided by publisher